(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The aim of this research is to investigate the factors affecting customer retention in the sector of health insurance. Five factors were taken in this research based on past studies in insurance sector; they are Insurance plans, Premiums, Services delivered, Employee Empathy and Reliability. At the beginning, T-test was conducted and according to the results obtained all the five factors mentioned were found to be significant. Then in order to cross verify the results obtained from T-test, multiple regressions was conducted taking Customer Retention as the dependent variable and the other five factors; Insurance plans, Premiums, Services delivered, Employee Empathy and Reliability as the independent variables. In multiple regression analysis, all the factors were found significant except Employee Empathy which was found to be of no significance. According to the results obtained in multiple regression analysis the null hypothesis which stated that “Employee Empathy has no role to play in Customer Retention” was accepted where as the other null hypotheses were rejected. So, in this study the Insurance plans, Premiums, Services delivered and Reliability emerged as the factors that affect the customer retention in health insurance sector.